Rancang Bangun Alat Penetralisir Asap Akibat Kebakaran Hutan Menggunakan Metode Corona Discharge - M. Nur Faizi; Syaiful Amri (Seminar Nasional Teknologi Informasi Komunikasi dan Industri, 2016)
The forest area in Bengkalis district has an area of around 463 441 ha, with a variety of natural resources that can be generated from the forest. But in recent years frequently burned forest bengkalis induced land clearing by companies or individuals who have a bad impact to masyaarakat, so that the smoke caused by forest fires have been a disaster for the community in terms of both economy and health. The worst impacts experienced is the disruption of the respiratory system, because in the smoke contained various types of hazardous and toxic gases. For that it is developing an instrument capable of neutralizing the smoke generator using ozone generated by corona discharge process. Ozone will ionize toxic gases into oxygen and cleanse the air of the process, so that this method can be said to be effective for the sterilization of air. There are several stages in this study, first: the system design. Second: the manufacture box. Third: the manufacture of power supply. Fourth: manufacture ozone generator, and the final testing of the tool to see the system working tool is functioning properly and can be used by the public, especially people Bengkalis district. Keywords: Bengkalis district, corona discharge, ionization, ozone(O3), smoke